How does the Green Deal affect the financial management of agribusiness entities? - Soliwoda, Michał; Grzelczak, Marlena (W poszukiwaniu zielonego ładu, 2022)
The aim of the study is to answer the question of how the Green Deal may affect the financial management of agribusiness entities, i.e. an economic area focused on the production of final food products. This approach allows for the identification of numerous interactions of agribusiness entities with the natural and social environment in rural areas. The chapter presents the essence of balance in reference to agribusiness entities, and a review of legislative and political initiatives related to the impact of the European Green Deal (EGD) on the agri-food sector. The added value of the study is an attempt to identify tools supporting agribusiness entities in achieving the goals resulting from the EGD.